Analisa Kelayakan Investasi Proyek Pembangunan Perumahan Berlian Kuok Sejahtera (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Project Housing development has growing fast, Not only in the central city but also in the suburbs area. PT. Tiga Berlian Sejahtera developing housing project at Jl. Pekanbaru-Bangkinang, Rimbo Panjang, Kab. Kampar. The object object of this research is Berlian Kuok sejahteraâs housing with 3 Ha area and 141 housing units will be marketed. This construction by using alternative is 30% equity and 70% loan. The purpose of this thesis is to determine investment feasibility of project housing development Berlian Kuok Sejahtera with indicator of investment feasibility using method Net Present Value (NVP), Benefit Cost Ratio (BCR), and Internal Rate of Return (IRR). Then, sensitivity level will be tested of investment, interest rate, benefit, and cost. From the financial terms, the return on investment with a period of 3 years can be fulfilled with a value of NPV Rp 2.141.123.359,44, IRR amount to 20,42%, and the BCR at 1,07. From the sensitivity analysis, housing development Berlian Kuok sejahtera still feasible to limit investment costs increased to 11,32%, the interest rate increased to 63,38%, the sensitivity of benefit decreased 9,47% and sensitivity of cost increased by 136,34%.Keywords : Investment, Housing, Investment Feasibility Analysis, Sensitivity Analysis, Berlian Kuok Sejahtera, Kampar.